1993
DOI: 10.1016/s0886-3350(13)80333-1
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of retinal detachment following extracapsular cataract extraction: A follow-up study with an analysis of risk factors

Abstract: We reviewed the medical records of 1,726 eyes consecutively operated on with extracapsular cataract extraction to examine the incidence of and the risk factors for retinal detachment (RD). In Denmark, both diagnoses and deaths are registered centrally; therefore, a complete follow-up was achieved in each case and actuarial statistical methods were used in the risk assessment. Seven eyes (0.41%) developed RD and 345 eyes (20.0%) had YAG-laser capsulotomy in the observation period, which averaged 39 months. We i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
1

Year Published

1994
1994
2012
2012

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(30 citation statements)
references
References 15 publications
0
29
1
Order By: Relevance
“…RD is one of the most significant and severe events that can occur after all forms of cataract surgery, including phacoemulsification. [16][17][18][19][20][21][22] Our previous study reported a 0.073% incidence of MHRD postphacoemulsification and IOL implantation in an unselected group of patients, 3 which is much lower than the 0.7% incidence of non-MHRD after cataract surgery by phacoemulsification according to a previous report by Ramos et al 23 All patients had metamorphopsia or sudden decreased central vision 9-74 months out after cataract surgery. Although 8 eyes had peripheral holes, we had not found any peripheral holes by routine fundus examination after cataract surgery and considered them as atrophic retinal holes, which are usually asymptomatic and do not progress to retinal detachment.…”
Section: Discussionmentioning
confidence: 88%
“…RD is one of the most significant and severe events that can occur after all forms of cataract surgery, including phacoemulsification. [16][17][18][19][20][21][22] Our previous study reported a 0.073% incidence of MHRD postphacoemulsification and IOL implantation in an unselected group of patients, 3 which is much lower than the 0.7% incidence of non-MHRD after cataract surgery by phacoemulsification according to a previous report by Ramos et al 23 All patients had metamorphopsia or sudden decreased central vision 9-74 months out after cataract surgery. Although 8 eyes had peripheral holes, we had not found any peripheral holes by routine fundus examination after cataract surgery and considered them as atrophic retinal holes, which are usually asymptomatic and do not progress to retinal detachment.…”
Section: Discussionmentioning
confidence: 88%
“…The reported risk factors were identical to those already mentioned for the intracapsular approach with the addition of ''capsulotomy'' and ''open posterior capsule''. In their own study Nielsen and Naeser (1993) observed a 0.41% incidence of RD with the risk factors ''age below 70 at the time of surgery'' and ''intraoperative complications'' during a 39 month follow-up. Sørensen and Baggesen (1990) found a 1.3% incidence of RD among 8350 eyes operated on with ICCE, while Ninn-Pedersen and Bauer (1996) observed a 0.71% risk among 5878 eyes operated on with ECCE or phakoemulcification.…”
Section: Discussionmentioning
confidence: 92%
“…Significant risk factors for RD were ''age below 70 at the time of surgery'' and ''myopia''. Nielsen & Naeser (1993) reviewed earlier papers over RD following ECCE; in studies published between 1985 and 1992 incidences of RD between 0.33 and 1.70% were reported. The reported risk factors were identical to those already mentioned for the intracapsular approach with the addition of ''capsulotomy'' and ''open posterior capsule''.…”
Section: Discussionmentioning
confidence: 99%
“…More than 1 surgical intervention may be required in more complex situations, such as bacterial endophthalmitis, early postoperative RD, or choroidal hemorrhage. [13][14][15][16][17][18][19][20][21][22] Following retention of lens fragments and associated problems, RD is the most common complication of cataract surgery. In the present study, approximately 85% of patients with RD had prolapse of the vitreous that was not treated during cataract surgery.…”
Section: Discussionmentioning
confidence: 99%